Analysis of Validation of Instruments to Measure Student’s Critical Thinking Ability and Science Literation - Tomi Widiatmo; A Wahab Jufri; Jamaluddin Jamaluddin (Postgraduate, University of Mataram, 2019)
Abstrak: This study aims to produce a valid and reliable instrument to measure the influence of guided inquiry learning models on students' critical thinking skills and scientific literacy through assignment techniques. The instruments of this study are a syllabus, learning implementation plan (RPP), questions of critical thinking and scientific literacy. An analysis of validity is carried out by proving the content and criteria validity. The results of the analysis of validity, reliability, level of difficulty, and differentiation indicate that the instrument has met the criteria that are feasible and valid for measuring students' critical thinking and literacy skills.Keywords: Validity; Research Instruments; Critical Thinking; Science Literacy; Guided Inquiry.